The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m100183200
|View full text |Cite
|
Sign up to set email alerts
|

A Mitogenic Signal Triggered at an Early Stage of Vaccinia Virus Infection

Abstract: Vaccinia virus (VV) triggers a mitogenic signal at an early stage of infection. VV-induced proto-oncogene c-fos mRNA with kinetics paralleling that stimulated by serum. The VV virokine, or vaccinia virus growth factor (VGF), was not crucial for c-fos induction because it was observed upon infection with the virokine-minus mutant VV (VGF ؊ ). Furthermore, c-fos expression did not require infectious virus particles, as it occurred even with UV-inactivated VV and was equally induced by the different multiplicitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 56 publications
4
31
0
Order By: Relevance
“…4A) or murine cells (not shown). Our observations for primary human cells agree with other reports using established cell lines (4,11,24). However, in addition to activating ERK and p38, eIF4E phosphorylation requires eIF4F assembly, illustrating the requirement for proper complex architecture to ensure that the activated kinase Mnk1 is properly oriented in respect to its substrate, eIF4E (35,43,47).…”
Section: Resultssupporting
confidence: 82%
“…4A) or murine cells (not shown). Our observations for primary human cells agree with other reports using established cell lines (4,11,24). However, in addition to activating ERK and p38, eIF4E phosphorylation requires eIF4F assembly, illustrating the requirement for proper complex architecture to ensure that the activated kinase Mnk1 is properly oriented in respect to its substrate, eIF4E (35,43,47).…”
Section: Resultssupporting
confidence: 82%
“…GM-CSF receptor activation is followed by Jak2 phosphorylation of receptor tyrosines and eventual activation of Stat5 and the MAPK pathways via Grb2, Shc, and SHP2 (66). Similarly, VACV is reported to be dependent on MAPK signaling for replication (45,46,47). We observed significantly decreased viral production with treatment of Akt and Erk inhibitors (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…VACV is dependent on Akt and Erk1/2 signaling pathways for entry and replication (45)(46)(47)(48). Since we have discovered that M1 and M2 cells are permissive to VACV, we sought to analyze the dependence of these two pathways on VACV replication in MDMs independent of binding and entry.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccinia MV enters cells through either endocytosis or plasma membrane fusion, depending on the involved virus strain (6,(8)(9)(10)51) and the cell type (7,22,(52)(53)(54). We previously showed that vaccinia MV of the WR strain enters HeLa and MEF cells through fluid-phase endocytosis, after which the internalized MV particles associate with PI3P-positive macropinosomes and Rab5-positive endosomes (19,20).…”
Section: Discussionmentioning
confidence: 99%